2019
DOI: 10.1515/tjj-2019-0035
|View full text |Cite
|
Sign up to set email alerts
|

Investigations of Combustor Inlet Swirl on the Liner Wall Temperature in an Aero Engine Combustor

Abstract: Experimental and numerical investigations are carried out on an annular, straight flow, swirl-stabilized aero engine combustor. In this work, the effect of degree and direction of swirl at the inlet of combustion chamber is examined on the liner wall temperature and hot spots. This is carried out by experimentally measuring the liner outer wall temperature at discrete positions along the circumferential and axial directions of the combustor liner in the engine test facility. The RANS based turbulence modeling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Different types of combustion chambers have been developed in the past century and different fuels are used there. In aero-engine or gas turbine combustor design, complete combustion, 1-3 low total pressure loss, 4 stability, 5,6 freedom from flash back and flame out, 7,8 relightabality, 9,10 occupying a small space, and no hot spots [11][12][13] are desired, and many researches have been performed on these areas to have better designs.…”
Section: Introductionmentioning
confidence: 99%
“…Different types of combustion chambers have been developed in the past century and different fuels are used there. In aero-engine or gas turbine combustor design, complete combustion, 1-3 low total pressure loss, 4 stability, 5,6 freedom from flash back and flame out, 7,8 relightabality, 9,10 occupying a small space, and no hot spots [11][12][13] are desired, and many researches have been performed on these areas to have better designs.…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that the flow condition from compressors have an obvious influence on the design of combustor and more attention should be focused on this by the designers. Rao et al 4 investigated the effect of compressor exit swirl on the liner wall temperature distribution in an aero engine combustor. They showed the development of hotspots on liner surfaces with the increase in swirl angle at the combustor inlet.…”
Section: Introductionmentioning
confidence: 99%
“…From the above literature review, it is clear that the compressor exit will always have some swirl [1][2][3][4] which cannot be neglected in analysing an actual combustor performance. The effect of various combustor design parameters such as fuel nozzle spray patterns, dilution hole geometry, fuel type, swirl number and different fuel injection methods on combustor exit pattern factor has been reported by authors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation